# how do you convert point slope form into standard form?

### 2 Answers | Add Yours

You need to remember what the point slope form of equation is:

`y - y_1 = m(x - x_1)`

The coordinates `(x_1,y_1)` represent the coordinate of the point that lies on the line and m expresses the value of the slope of the line.

You need to remember what the standard form of equation is:

`ax + by + c = 0`

You need to convert the point slope form into the standard form, hence, you need to bring all terms to one side, open the brackets and then you need to collect like terms such that:

`y - y_1 - mx + mx_1 = 0`

You need to remember that `x_1,y_1` and m are all value, hence the standard form is:

`-mx + y - (y_1 - mx_1) = 0`

`mx - y + (y_1 - mx_1) = 0`

**Hence, converting the point slope form in standard form of equation of line yields `mx - y + (y_1 - mx_1) = 0.` **

**Sources:**

standard form -Ax + By = C, where A, B, and C are all integers (whole numbers)

Ex.) y - 1 = 3x - 12

3x - y =11